Tourism Development Strategy Through 3A Elements in Sunan Kalijaga Religious Tourism Object - Hasanah, Lailatul; Susanto, Dedy; Niswah, Uswatun; Hakim, Lukmanul (Munazzama: Journal of Islamic Management and Pilgrimage, 2023)
One of the tourism potentials that is currently developing is religious tourism. The religious tourism in Demak Regency is the Tomb of Sunan Kalijaga. Each tourism object has its own uniqueness and characteristics, but cannot be separated from the existing 3A elements (attractions, amenities, accessibility). In the religious tourism object, Sunan Kalijaga Tomb has implemented elements of 3A even though there are several deficiencies that have not been fulfilled. The development strategy at Sunan Kalijaga Tomb is carried out by the foundation itself, therefore there is a need for a tourism development strategy that must be carried out to develop religious tourism at Sunan Kalijaga Tomb. Considering the tourism development strategy through 3A elements, this article focuses on the tourism development strategy through 3A elements in the religious tourism object of Sunan Kalijaga Tomb. The study aims to determine the implementation of 3A elements (Attractions, Amenities, Accessibility) of Sunan Kalijaga Tomb as a religious tourism destination in Demak regency and tourism development strategy through elements of 3A (attractions, amenities, accessibility) at religious tourism objects of Sunan Kalijaga Tomb in Demak regency.The type of research used was descriptive qualitative. Types and sources of data used were primary data sources and secondary data sources. Data collection techniques were observation, interviews and documentation. The data was collected and analyzed using data analysis techniques which include data reduction, presentation stage, and conclusion verification. The results of the study show that: 1) The implementation of 3A elements (attractions, amenities, and accessibility) at the religious tourism object of Sunan Kalijaga Tomb was adequate, but there were still some deficiencies. As religious tourism attractions, Sunan Kalijaga Tomb had an attraction in the form of the culture Sunan Kalijaga taught, the architecture of the building and the figure of Sunan Kalijaga, who was very well known by the people around the area. The amenities provided, such as shoe storage, mosques, bathrooms, parking lots, were adequate, but there were still deficiencies that had not been met. Accessibility to the tomb of Sunan Kalijaga was quite good. The condition of the road that had been paved and easily accessible for visitors who wanted to come. 2) The strategy for developing tourism through the 3A elements at the Tomb of Sunan Kalijaga was divided into 3 aspects; they are the strategy for developing the economic sector, the strategy for developing the religious sector, and the strategy for developing the socio-cultural sector. These three aspects had been going well, but there were some deficiencies that needed to be corrected for better results in the future.